Current state and directions of further circular agricultural economy development in Ukraine - Степаненко, С. В.; Кузьома, В. В.; Тимошенко, К. В. (My University, 2023)
The subject of the study is the analysis and development of the circular agricultural economy of Ukraine. Methodology. The study uses general scientific methods, in particular: theoretical generalisation; methods of positive-normative analysis and statistical analysis. The purpose is to assess current trends in the circular economy in the agricultural sector of Ukraine and to substantiate the directions of its further development. Research conclusion. Achieving the global sustainable development goals, to which Ukraine has joined, requires the search for and implementation of new business models aimed at ensuring the interests of current and future generations. The agricultural sector is of utmost importance in addressing these challenges, as it contributes to solving the problem of hunger, ensuring food security and improving the quality of life of the world's population. The article provides an overview of the current problems of development of the agro-circular economy, which is proposed to be considered as one of the tools for achieving the goals of sustainable development. The main problematic aspects that impede the intensification of agro-circular transformations in Ukrainian agriculture are identified. The article compares certain indicators of the level of agro-circularity in the EU and Ukraine. An analysis of the current state of development of the circular economy in Ukrainian agriculture is carried out. On the basis of economic and statistical models, the level of dependence of agricultural production on the use of new material resources is studied. The obtained results show low rates of development of circular processes in the agricultural sector of Ukraine and a high level of consumption of input resources. The study of the methodological basis for assessing the state of development of the closed-type agro-economy has allowed to propose the authors' vision of systematisation of indicators of the level of development of circular processes in agriculture. This systematisation was based on the identification of five main dimensions: consumption of new materials, waste volumes, agricultural waste management, economic efficiency, and state financial support. The study identified key priority areas for further development of the agro-circular economy in Ukrainian agriculture.
Web of Science
Keywords: agriculture; closed economy; sustainable development; resources; agricultural companies; agro-circular processes